Integrating sharia financial mechanisms with indonesia's halal economy: Opportunities, challenges, and strategies for sustainable growth - Cecep Bryan Firdaus (Journal of Islamic Economic Insights, 2025)
This study emphasizes the interconnected relationship between the Halal Economy and Islamic Financial Mechanisms, proposing that Indonesia should strategically incorporate Sharia financial mechanisms to advance its halal economy. By following Islamic finance principles, Indonesia can allure foreign investment, encourage ethical business conduct, and fulfil the increasing demand for halal products and services worldwide. Despite advancements in Indonesia's halal industry development, challenges such as the requirement for specialized expertise and strong regulatory frameworks continue to exist. However, through deliberate integration and targeted investments in education and infrastructure, Indonesia can establish itself as a key player in the global halal market. This will drive economic growth, while improving sustainable development efforts and enhancing global competitiveness.